Use of mango seed almonds to obtain pastry oil - Sanz M., Eileen Chiquinquirá; Dix S., Diana Isadora; Robayo R., Aycardo Emilio; Bernal L., Oscar Javier; Carrillo V., Jorge Eliecer (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The Mango residues, the result of fruit processing processes, are normally not processed because they have no industrial value for the production of juices, jams, among other derivatives; contributing to environmental problems when they are not adequately disposed of. For this reason, this research was raised; the objective of which was to take advantage of the seeds residues of the Tommy Atkins variety mango (Mangífera indica L.), for the production of useful oils in the production of pastry products. To carry out the oil extraction, a Soxhlet extractor with hexane of 99 % purity at a boiling point between 68-75 ° C was used. Among the results obtained, it was found that the oil has stearic fatty acid (40.4 ± 0.01 g.100 g-1) in a higher proportion, followed by oleic (33.6 ± 0.02 g.100 g-1), palmitic (12,0 ± 0.01 g.100 g-1), linoleic (8.1 ± 0.2 g.100 g-1), linolenic (1.6 ± 0.02 g.100 g-1) and finally arachidic acid (3.0 ± 0.04 g.100 g-1). From the oil obtained, traditional formulations for pastry products such as chocolate truffles, Genovese, ganache and quick chocolate biscuit were made, replacing 100 % of commercial sunflower oil. Subsequently, the acceptance of the products was tested, through a sensory evaluation, applied to 50 untrained panelists, who compared the products made with commercial oil versus those made with mango almond oil; the most widely accepted being the use of the latter in ganache (60 %) and chocolate truffles (64 %).